Vietnam after the fire - Miller, J. Edward (New York Cinema Guild, 1988)
A documentary of four parts that shows how Vietnam now under the Communist rule is surveying after the war in particular on its environment.
Narrated by Eartha Kitt,; translation, Vu Binh, Nguyen Quang Dy, Dinh Thi Hoa, Thanh Thi Kent, Tam Vu.
Keywords: Environemental protection -- Vietnam; Forests and forestry -- Vietnam; Forest management -- Vietnam